Can Molecular Genetic Evidence Influence Jurors’ Perceptions of a Defendant? Results From a Randomized Experiment - Costa, Elise T. (Criminal justice and behavior, 2017)
Despite increases in genetic evidence being used as mitigating or aggravating factors in criminal cases, few studies have examined whether evidence of a defendant’s genotype influences legal decision making of jurors. Using a randomized experiment, this study examined whether potential jurors’ legal decisions are affected when a defendant’s molecular genetic information is entered as mitigating evidence. Participants served as potential jurors from two universities (N = 279). Results from multivariate regression models suggest that genetic evidence does not influence punitive attitudes toward a defendant. However, genetic evidence did have a statistically significant effect on fearfulness of the defendant. Participants assigned to the condition in which evidence of the defendant possesses genetic risk of criminality and a history of child abuse were the most fearful of the defendant. We conclude by describing how our findings are related to past research, and we also discuss implications of our study for future research.